3D in-vitro cultures of human bone marrow and Wharton’s jelly derived mesenchymal stromal cells show high chondrogenic potential - Lamparelli, Erwin Pavel; Ciardulli, Maria Camilla; Giudice, Valentina; Scala, Pasqualina; Vitolo, Rosa; Dale, Tina Patricia; Selleri, Carmine; Forsyth, Nicholas Robert; Maffulli, Nicola; Della Porta, Giovanna (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, chondrogenic potentials of 3D high-density cultures of Bone Marrow (BM) and Wharton’s Jelly (WJ)-derived mesenchymal stromal cells (MSCs) was investigated by chondrogenesis- and cytokine-related gene expression over a 16-day culture period supplemented with human transforming growth factor (hTGF)-β1 at 10 ng/mL. In BM-MSC 3D models, a marked upregulation of chondrogenesis-related genes, such as SOX9, COL2A1, and ACAN (all p < 0.05) and formation of spherical pellets with structured type II collagen fibers were observed. Similarly, WJ-based high-density culture appeared higher in size and more regular in shape, with a significant overexpression of COL2A1 and ACAN (all p < 0.05) at day 16. Moreover, a similar upregulation trend was documented for IL-6 and IL-10 expression in both BM and WJ 3D systems. In conclusions, MSC-based high-density cultures can be considered a promising in vitro model of cartilage regeneration and tissue engineering. Moreover, our data support the use of WJ-MSCs as a valid alternative for chondrogenic commitment of stem cells in regenerative medicine.